2009
DOI: 10.1038/ja.2008.6
|View full text |Cite
|
Sign up to set email alerts
|

Genetic analysis of Helicobacter pylori clinical isolates suggests resistance to metronidazole can occur without the loss of functional rdxA

Abstract: Resistance to metronidazole (MTZ) in Helicobacter pylori is associated with mutations in rdxA, encoding an oxygen-insensitive NADPH nitroreductase, and mutations in frxA, encoding a NAD(P)H-flavin oxidoreductase. Despite this association, the strict correlation of MTZ resistance with mutations in rdxA or frxA is still controversial. In this study, rdxA allelic replacement was used to distinguish resistance-associated nucleotide mutations from the natural genetic diversity of H. pylori. Replacement with truncat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
17
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 40 publications
4
17
0
1
Order By: Relevance
“…The most commonly used treatments include bismuth salts, H2 receptor antagonists and proton pump inhibitors such as omeprazole, lansoprazole and pantoprazole. Amoxycillin, tetracycline, metronidazole and clarithromycin are the most effective therapies for this infection (11)(12)(13). Meanwhile, the treatment of H. pylori infection does not always eradicate the organism.…”
Section: Introductionmentioning
confidence: 99%
“…The most commonly used treatments include bismuth salts, H2 receptor antagonists and proton pump inhibitors such as omeprazole, lansoprazole and pantoprazole. Amoxycillin, tetracycline, metronidazole and clarithromycin are the most effective therapies for this infection (11)(12)(13). Meanwhile, the treatment of H. pylori infection does not always eradicate the organism.…”
Section: Introductionmentioning
confidence: 99%
“…Such resistance clearly decreases the effectiveness of Mtz-containing anti-H. pylori therapies, which tend to be popular because they are relatively inexpensive (Kim et al, 2009).…”
mentioning
confidence: 99%
“…If patients infected with Mtz-susceptible H. pylori are treated with the drug, reduction of the nitro moiety of the Mtz produces highly reactive compounds that cause DNA strand breakage, helix destabilization, helix unwinding and, ultimately, death of the bacterial cells (Kwon et al, 2001;Kim et al, 2009). Acquisition of Mtz resistance by H. pylori is highly associated with mutational inactivation of the bacterium's rdxA gene, which encodes an oxygen-insensitive NADPH nitroreductase (Tankovic et al, 2000).…”
mentioning
confidence: 99%
“…Mutations of rdxA , a gene that encodes an oxygen-insensitive NADPH nitroreductase, were the main cause of H. pylori resistance to metronidazole (Goodwin et al, 1998). Additionally, the inactivation of frxA (encoding the NADPH flavin oxidoreductase) and fdxB (encoding the ferredoxin-like protein) may also induce H. pylori resistance to metronidazole (Kim et al, 2009). Recently, Mehrabadi et al assessed the role of the resistance nodulation cell division (RND) family efflux pump in the metronidazole resistance of H. pylori using RT-PCR; they reported that excess amounts of metronidazole increased the gene expression levels of the outer-membrane protein (TolC) homologs of RND pumps (Mehrabadi et al, 2011).…”
Section: Helicobacter Pylori Recurrencementioning
confidence: 99%